Permits application process for construction at Majlis Perbandaran Taiping (MPT) / Nurul Athirah Ibrahim - Ibrahim, Nurul Athirah (Universiti Teknologi MARA UiTM,Perak, 2021)
For every construction projects that runs within the Majlis Perbandaran Taiping jurisdiction, the contractors of the project should be responsible for the permit application for the said construction projects. This is because the permits are one of the important documents that needed to be owned by the contractors in the construction duration. There are three main permits that conveys the similar uses between each of it but the permit is used for different type of construction projects. The three main permits that will be introduce in this report are construction permit, construction materials permit and small construction work permit. These permits acts as a free pass for the contractors to runs the construction albeit all situation. All of this permits are managed under the building department of this municipal council. Mr. Hisham, the head of building department along with Mr. Nizwal, Mr. Helmy and Mr. Norazmi are the one who has given the power to validate the said permit. Other than that, there are several problems that may be faced by the user of the permits regarding the permit for the construction. Nevertheless, the problems may be solved as the contractors could come to building department and seek a consultation from the related staffs. To recapitulate, this report will explain completely the steps on the way to applying the permit process as well as the its uses and problems that may rise regarding this three permits.